2008
DOI: 10.1021/ol8015379
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functionalization of 3,3′-Bis(spirodienone)-Bridged 2,2′-Bithiophene: A New Building Block for Redox-Active Molecular Switching Materials

Abstract: Bithiophene derivatives bridged with a bis(spirodienone) unit were synthesized and characterized. Lithiation of the thiophene rings of an unsubstituted derivative proceeded without decomposition of the bis(spirodienone) skeleton. Palladium-catalyzed cross-coupling reactions (Suzuki-Miyaura, Sonogashira) with bromides afforded a variety of pi-extended derivatives. Bond breaking and formation under redox conditions were observed by cyclic voltammetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Thiophene-containing organic compounds such as oligothiophenes, polythiophenes, and fused thiophenes have emerged as useful building blocks for electronic, optoelectronic, sensing, and molecular switching materials. Synthesis and functionalization of oligothiophenes have been extensively investigated because of the utilization of the π-conjugated systems. Extension of the π conjugation and modification of the thiophene ring are important issues in the area of thiophene-based materials. On the other hand, alkynes are useful starting materials for the preparation of π-conjugated organic compounds. , Late-transition-metal complexes catalyze addition reactions of thioesters and sulfides to alkynes via C–S bond cleavage. , However, only a few studies have been reported on metal-catalyzed reactions of thiophenes with alkynes. , …”
mentioning
confidence: 99%
“…Thiophene-containing organic compounds such as oligothiophenes, polythiophenes, and fused thiophenes have emerged as useful building blocks for electronic, optoelectronic, sensing, and molecular switching materials. Synthesis and functionalization of oligothiophenes have been extensively investigated because of the utilization of the π-conjugated systems. Extension of the π conjugation and modification of the thiophene ring are important issues in the area of thiophene-based materials. On the other hand, alkynes are useful starting materials for the preparation of π-conjugated organic compounds. , Late-transition-metal complexes catalyze addition reactions of thioesters and sulfides to alkynes via C–S bond cleavage. , However, only a few studies have been reported on metal-catalyzed reactions of thiophenes with alkynes. , …”
mentioning
confidence: 99%
“…1,2‐Dispirodienones 64 derived from bithiophenes have been shown by electrochemistry to ring‐open (to form 65 ) and ring‐close ( 65 → 64 ) under redox conditions [Scheme , Equation (1)]. Consequently, these molecules could serve as molecular switching materials 7b,7c. To investigate the redox properties of the 1,2‐dispirodienone 10 , we performed electrochemical experiments to determine if bond breaking and bond formation can occur under redox conditions [Scheme , Equation (2)].…”
Section: Resultsmentioning
confidence: 99%
“…The tert ‐butyl groups are crucial for the stability of these compounds. Interestingly, studies of the redox properties of these molecules have shown that they could be used as molecular switches 7b,7c…”
Section: Introductionmentioning
confidence: 99%
“…Following this second route, an enhancement of the yield was obtained, going from 33% to 67%. These syntheses were preferred to the Suzuki-Miyaura coupling recently reported [26] because of the difficulty to obtain 3,5-di-tert-butyl-4-hydroxyphenylboronic acid as a pure product in high yields.…”
Section: Synthesismentioning
confidence: 99%